145 Masters athletes demonstrate sex differences in aortic stiffness. (6th June 2022) - Hughes, Rebecca; Ojrzynska-Witek, Natalia; Augusto, Joao; Bhuva, Anish; Parry-Williams, Gemma; Papatheodorou, Stathis; D'Silva, Andrew; Torlasco, Camilla; Manisty, Charlotte; Hughes, Alun; Sharma, Sanjay; Moon, James
Abstract : Introduction: Aortic stiffening increases with sedentary age and is associated with cardiovascular disease. Lifelong exercise counteracts this – at least in male masters athletes, but the impact in females is unknown. Methods: We measured aortic compliance in male and female masters athletes (n=305, mean age 53.9) and healthy controls (n=50), measuring Pulse Wave Velocity (PWV), aortic distensibility and beta-stiffness (β, a blood pressure independent measure of aortic stiffening). Masters athletes were defined as age ≥40, exercised systematically for >10 years and competed in >10 endurance events. Male and female athletes were recruited from the same sporting bodies. CMR was performed at 1.5T, measuring arterial stiffness at ascending, proximal descending and distal descending aorta (Ao-A, Ao-P, Ao-D. Biological vascular age was derived from correlating distensibility with chronological age. Results: All central blood pressure parameters were lower in athletes. Athletes demonstrated expected cardiac adaptation (higher indexed end diastolic, end systolic and stroke volumes, and indexed LV mass, all P<0.005). PWV and aortic distensibility was equivalent to controls at every aortic level. β was also equivalent, except at Ao-D, where athletes were stiffer (median (IQ range) 3.06 x10–3 mmHg-1 (2.54–3.81) vs 2.63 x10–3 mmHg-1 (2.18–3.21), P<0.005. Masters athletes demonstrated sex differences in aortic stiffness with female athletes demonstrating increased distensibility at Ao-P and Ao-D compared with male athletes (P=0.008, P<0.001 respectively), and lower β (P=0.009, P<0.001). PWV was equivalent between both sexes. Male masters athletes were biologically older than their chronological age at each aortic level (3.8 years at Ao-A, 8.7 years at Ao-P and 1.0 years at Ao-D). Female masters athletes were biologically younger than their chronological age in the Ao-A (-0.5 years) and Ao-D (-6.2 years) and older in the Ao-P, but by a smaller order of magnitude than males (2.5 years). Conclusion: Regular exercise to masters athlete level in older age is associated with a sex specific effect on aortic compliance compared with matched non-athletes, with males demonstrating a significant increase in vascular age at each aortic level compared with females. Female masters athletes exhibit age-reversal in the distal descending aorta (-6.2 years). Conflict of Interest: nil